Revealing of Hepatitis, A and E virus among Restaurant and Bakeries workers - Sattar Gaber Ajeel,; Rusul Sahib Hussien Mohmmed Shubber, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Hepatitis , ( HAV and HEV ) interracially transmitted causes inflammation of liver that can causes mild to severe illness ,the two viruses transmitted through ingestion of contamination food and drinking of contamination of water , also infection happen via direct contact with the person infected with virus .The viruses spread through stool (feces / urine) that contaminated with viruses . However , the food handlers (Restaurant and Bakeries workers) infection with hepatitis A and E were frequently identified and need immunoprophylais , also need implementation for control are aconsiderableburdenon the public health resources and the viruses (A,E) are source of hepatitis for unknown proportion for the person who source infection . this study aim to reveal of the present of viruses and synergistic concordant of the infection with both viruses (A,E) apparently the healyhy group (control group ) blood were collection from 50 persons infection with (HAV and HEV ) as patients group and 50 samples from 50 personse as control group (healthy donor , (10 sample were destroy . All samples were tested by ELISA test from detection of hepatitis type ( A and E ) the co-infection of two virus revealed in hepatitis virus patients and and control group with exposure rate 30 (60.0%) and 5 (10.0%) respectively . Methods: This study dependent on samples that taken from (50) persons that divided for detection of two viruses (A and E ) the first tube for revealing of HAV and the second tube for revealing of HEV for the present of IgM anibody for each tubes and compared with the (50) samples that taken from relative who come to hospital used as control group (healthy blood donors group). Conclusions: We abstained result from serological reveal from serum of persons those for present of HAV and HEV